A rodent model of HIV protease inhibitor indinavir induced peripheral neuropathy. Issue 1 (23rd September 2016) - Huang, Wenlong; Calvo, Margarita; Pheby, Tim; Bennett, David L.H.; Rice, Andrew S.C.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Rats treated with HIV antiretroviral drug indinavir demonstrated alterations in neuropathic pain-related sensory and thigmotactic behaviours accompanied by significant loss of hind paw skin sensory innervation. Abstract: HIV-associated sensory neuropathy (HIV-SN) is the most frequent manifestation of HIV disease. It often presents with significant neuropathic pain and is associated with previous exposure to neurotoxic nucleoside reverse transcriptase inhibitors. However, HIV-SN prevalence remains high even in resource-rich settings where these drugs are no longer used. Previous evidence suggests that exposure to indinavir, a protease inhibitor commonly used in antiretroviral therapy, may link to elevated HIV-SN risk. Here, we investigated whether indinavir treatment was associated with the development of a "dying back" axonal neuropathy and changes in pain-relevant limb withdrawal and thigmotactic behaviours. After 2 intravenous injections of indinavir (50 mg/kg, 4 days apart), adult rats developed hind paw mechanical hypersensitivity, which peaked around 2 weeks post first injection (44% reduction from baseline). At this time, animals also had (1) significantly changed thigmotactic behaviour (62% reduction in central zone entries) comparing with the controls and (2) a significant reduction (45%) in hind paw intraepidermal nerve fibre density. Treatment with gabapentin, but not amitriptyline, was associated with a complete attenuation of hind paw mechanical hypersensitivity observed with indinavir treatment. Furthermore, we found a small but significant increase in microglia with the effector morphology in the lumbar spinal dorsal horn in indinavir-treated animals, coupled with significantly increased expression of phospho-p38 in microglia. In summary, we have reported neuropathic pain-related sensory and behavioural changes accompanied by a significant loss of hind paw skin sensory innervation in a rat model of indinavir-induced peripheral neuropathy that is suitable for further pathophysiological investigation and preclinical evaluation of novel analgesics.